2021
DOI: 10.3390/ma14051265
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of PSC Structures from FRP with a Prestressing Strengthening Method

Abstract: A prestressed concrete (PSC) structure is subject to prestress losses in the long and short terms, and the structure ages over time. The structure is susceptible to corrosion from exposure to environmental factors such as moisture, chloride, and carbonation, thus causing prestress loss. Therefore, strengthening the structure is needed to address this problem. Here, the near surface mounted (NSM) method and the external prestressing (EP) method were selected because they are capable of applying additional prest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The NSM method strengthens a structure by creating grooves with a constant depth and embedding FRP plates or FRP rods instead of attaching reinforcement on the concrete surface, as in the existing EB method. Kim et al [ 18 ] reported that the NSM method affords a relatively higher performance improvement than the EB method owing to its superior resistance to bond failure. Moreover, they reported that damage due to fire or vehicular collision could be avoided, unlike in the case where the reinforcement is bonded on the surface, because the reinforcement is embedded in the concrete.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NSM method strengthens a structure by creating grooves with a constant depth and embedding FRP plates or FRP rods instead of attaching reinforcement on the concrete surface, as in the existing EB method. Kim et al [ 18 ] reported that the NSM method affords a relatively higher performance improvement than the EB method owing to its superior resistance to bond failure. Moreover, they reported that damage due to fire or vehicular collision could be avoided, unlike in the case where the reinforcement is bonded on the surface, because the reinforcement is embedded in the concrete.…”
Section: Methodsmentioning
confidence: 99%
“…In both these methods, additional prestressing is applied upon completing construction. With regard to FRPs, glass fiber-reinforced polymers, such as aramid FRPs (AFRPs) and carbon FRPs (CFRPs) have been used as major strengthening materials [ 18 ]. FRPs exhibit brittle failure but have superior strength, weight, durability, creep, and fatigue resistance, compared to existing construction materials [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 17 displays the step-by-step procedure for applying externally prestressed CFRP for structural strengthening [ 212 ]. Kim et al [ 213 ] carried out research to address prestress losses and aging in prestressed concrete structures (PSCs); strengthening methods such as NSM and EP were used, utilizing FRPs, particularly CFRPs, for their non-corrosive and high tensile strength properties. The NSM and EP methods remarkably improved the stiffness by 50–60% compared to the control PSC specimen.…”
Section: Strengthening Techniquesmentioning
confidence: 99%
“…Table 1 shows the load-displacement test results of PSC structures reinforced with FRPs by Kim et al [ 31 , 32 , 33 ]. Four-node tests were also conducted.…”
Section: Ductility Index Evaluationmentioning
confidence: 99%
“…With the application of the EP method, cracks occurred at the anchorage. Therefore, it is thought that EP and NSM methods will show improved strengthening effects when these practical problems are resolved [ 31 ].…”
Section: Ductility Index Evaluationmentioning
confidence: 99%